Sustentación de caso: propuesta de un plan estratégico del ingreso al mercado peruano de una empresa del sector fast fashion - Corrales Nieves Polo, Jimena Maria (2018)
In an increasingly, competitive and constantly growing market, fashion companies have a great challenge for the penetration of new markets and the satisfaction of markets they are currently in.With an increasingly digitalized and demanding audience, fashion stores must innovate more and improve in different processes like acquisition of materials,production, logistics, price, sales, design, among others that finally seek more than satisfy their customer, they look for loyalty and maintain an increase in sales over time without neglecting the profitability of the business.Fast Fashion companies today have a great challenge and in Peru the competition for price, promotions and benefits are those that begin to lead the preference of many consumers of these brands and in general in clothing brands in the retail world.In the exposed work, the Fast Fashion business willbe analyzed with the example of the company Fast Retailing and its icon brand UNIQLO, a Japanese company that serves businesses in different cities around the world on different continents. We will validate the possible entry into the Peruvian market.Forthis, through an overview of the business and the application of management strategies, the feasibility of entering a very competitive market will be analyzed, where there is not only a very qualified local production, with low prices and in trend, but other international brands recognized that seek to increase their participation among the Peruvian market.The work is divided into 4 large blocks that help to understand both the business and the market and its needs, starting with an internal and external diagnosis of the company through the analysis of the value chain and the determination of strengths and weaknesses, opportunities and threats.Following the aforementioned comes the strategic formulation where, thanks to different matrices such as the SWOT, EFI, EFE and generic strategies we can draw some conclusions about the needs of the company in addition to the opportunities it would have for entering the Peruvian market.Then, we will see witch strategies to apply to combat and against subtracting our weaknesses and threats and to highlight and take advantage of our strengths and opportunities. The combination of different strategies from the most macro as global, corporate and business to micro as the functional ones, concluded that the entry of this fast fashion to the Peruvian market was feasible. Finally, through a control strategy and the support of a comprehensive balance scorecard, control can be defined for each area of the business and thus improving the entry and maintenance plan for the establishment in the Peruvian market.